Diagnosis of Carnitine Deficiency in Extremely Preterm Neonates Related to Parenteral Nutrition: Two Step Newborn Screening Approach - Mamatha Ramaswamy; Victor Anthony Skrinska; Rola Fayez Mitri; Ghassan Abdoh (MDPI AG, 2019)
Currently, there is no evidence in the literature to support the routine supplementation of all parenterally fed premature infants with l-carnitine. In our study, we found that about 8.56% of extremely preterm neonates are diagnosed with carnitine deficiency secondary to malnutrition, either due to reduced stores at birth or related to total parenteral nutrition (TPN). Our two step approach of performing newborn screening (NBS) again at 32 weeks gestational age (GA) equivalent helps to diagnose 81.4% more preterm babies with carnitine deficiency—who would otherwise be missed—and supplement them with l-carnitine for optimal growth. We performed a retrospective cohort study to diagnose carnitine deficiency related to malnutrition in two groups: those presenting at birth and those presenting later in life. We found that there was a statistically significant difference in the median GA and birth weight (BW) between the two groups, but there was no difference in the free carnitine levels.